2020
DOI: 10.1016/j.omtn.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

LNC473 Regulating APAF1 IRES-Dependent Translation via Competitive Sponging miR574 and miR15b: Implications in Colorectal Cancer

Abstract: A growing number of studies have focused on the involvement of non-coding RNAs (ncRNAs) in the internal ribosome entry site (IRES)-mediated translation in tumorigenesis; however, the underlying mechanisms in colorectal cancer (CRC) remain elusive. In this study, we show that LINC00473 (LNC473) exerted its functions as a tumor suppressor in promoting apoptotic protease-activating factor 1 ( APAF1 ) IRES activity through competitively sponging miR574-5p and miR15b-5p in CRC initiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In addition, we found in primary colorectal tumors that the hypermethylation of LINC00473 was associated with a decrease in the expression of this lncRNA. These results are in line with a previous work, which identified the downregulation of expression and tumor suppressor properties of LINC00473 in association with the initiation and pathogenesis of CRC [ 15 ]. Similarly, other authors have found epigenetic deregulation of important TSGs, such as p16/CDKN2A and hMLH1 , throughout the colorectal carcinogenesis process [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, we found in primary colorectal tumors that the hypermethylation of LINC00473 was associated with a decrease in the expression of this lncRNA. These results are in line with a previous work, which identified the downregulation of expression and tumor suppressor properties of LINC00473 in association with the initiation and pathogenesis of CRC [ 15 ]. Similarly, other authors have found epigenetic deregulation of important TSGs, such as p16/CDKN2A and hMLH1 , throughout the colorectal carcinogenesis process [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…LINC00473 is a lncRNA with pro-apoptotic tumor suppressor properties in CRC whose expression is downregulated in this tumor type. This lncRNA is able to sponge endogenous miR574-5p or miR15b-5p, inhibit cell proliferation and colony formation capacity, and induce cell apoptosis by activating the APAF1-CASP9-CASP3 pathway [ 15 ]. In addition, a genome-wide analysis of the CRC cell line HCT-116 recently identified promoter hypermethylation of LINC00473 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shang et al (115) found that the tumor-derived exosome, circPACRGL, acts as a sponge molecule of miR-142-3p/miR-506-3p, promoting the propagation, diversion, invasion, and adhesion of CC cells and N1 to N2 neutrophil differentiation. Wu et al (116) showed that the LNC473-MIR574/miR15B-APAF1 IRES signaling axis could manipulate the propagation and apoptosis of CRC cells to influence the initiation and progression of CRC. In this study, a ceRNA regulatory network was constructed with 1 lncRNA, 5 miRNAs, and 3 mRNAs, revealing the potential regulatory mechanism of lncRNA-miRNA-mRNA in CC, and indicating the direction for further exploration of the pathogenesis of CC.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic peptidase activating factor 1 (APAF1) is a core pro-apoptotic factor in the cytochrome C-dependent apoptosis signaling pathway [ 41 ]. Its expression is significantly downregulated in many tumors, suggesting that it is a tumor suppressor gene [ 42 ]. Induction of apoptosis is an important goal in tumor therapy.…”
Section: Discussionmentioning
confidence: 99%